MONITORAMENTO DA SALINIDADE NO AQUÍFERO CABO, NA REGIÃO COSTEIRA DA PLANÍCIE DO RECIFE (PE) - Montenegro, Suzana M. G. L.; Montenegro, Abelardo A. de A.; Cabral, Jaime J. da S. P.; Demétrio, José G. A.; Manoel Filho, João; Lima, Edmilson Santos de; Oliveira, Emanuelle M. de; Paiva, Anderson (Águas Subterrâneas, 2001)
Resumo não siponível.